Therapeutic targeting of chronic kidney disease-associated DAMPs differentially contributing to vascular pathology - Mazzarino, Morgane; Cetin, Esra; Bartosova, Maria; Marinovic, Iva; Ipseiz, Natacha; Hughes, Timothy R.; Schmitt, Claus Peter; Ramji, Dipak P.; Labéta, Mario O.; Raby, Anne-Catherine (Frontiers in Immunology, 2023)
Chronic Kidney Disease (CKD) is associated with markedly increased cardiovascular (CV) morbidity and mortality. Chronic inflammation, a hallmark of both CKD and CV diseases (CVD), is believed to drive this association. Pro-inflammatory endogenous TLR agonists, Damage-Associated Molecular Patterns (DAMPs), have been found elevated in CKD patients’ plasma and suggested to promote CVD, however, confirmation of their involvement, the underlying mechanism(s), the extent to which individual DAMPs contribute to vascular pathology in CKD and the evaluation of potential therapeutic strategies, have remained largely undescribed. A multi-TLR inhibitor, soluble TLR2, abrogated chronic vascular inflammatory responses and the increased aortic atherosclerosis-associated gene expression observed in nephropathic mice, without compromising infection clearance. Mechanistically, we confirmed elevation of 4 TLR DAMPs in CKD patients’ plasma, namely Hsp70, Hyaluronic acid, HMGB-1 and Calprotectin, which displayed different abilities to promote key cellular responses associated with vascular inflammation and progression of atherosclerosis in a TLR-dependent manner. These included loss of trans-endothelial resistance, enhanced monocyte migration, increased cytokine production, and foam cell formation by macrophages, the latter via cholesterol efflux inhibition. Calprotectin and Hsp70 most consistently affected these functions. Calprotectin was further elevated in CVD-diagnosed CKD patients and strongly correlated with the predictor of CV events CRP. In nephropathic mice, Calprotectin blockade robustly reduced vascular chronic inflammatory responses and pro-atherosclerotic gene expression in the blood and aorta. Taken together, these findings demonstrated the critical extent to which the DAMP-TLR pathway contributes to vascular inflammatory and atherogenic responses in CKD, revealed the mechanistic contribution of specific DAMPs and described two alternatives therapeutic approaches to reduce chronic vascular inflammation and lower CV pathology in CKD.